Correlação entre a lateralidade e a preferência lateral na virada olímpica do nado crawl - Lidiane Aparecida Fernandes (2021)
The swimming turn is a sequence of movements performed simultaneously as the swimmer approaches the turning end of the pool to return to the starting end. Aiming to analyze the lateral preference in the swimming turn with the manual and foot lateral preference, the present study aimed to investigate the lateral preference of swimmers who perform the crawl turn. In order to analyze the body lateral preference, aiming to understand if the manual and foot lateral preference are related to the lateral trunk preference, the IPLAG (Global Lateral Preference Inventory) questionnaire was applied to evaluate the lateral preference of the trunk and the lower and upper limbs. After applying the questionnaire, we observed the participants' turn. The sample consisted of 10 swimmers of both sexes, aged between 18 and 35 years. Preference means were calculated following the IPLAG. Regarding the mean of the general preferences and the frequency of turns, an inverse effect in the laterality was observed. In other words, the individuals were classified as right-handed and presented trunk preference to the left. Assessing the lateral preference at the swimming turn allows broadening the understanding of lateralized swimming behavior. Thus, understanding the athlete’s preference allows the elaboration of teaching strategies for the technical elements of the modality.